Analysis of Factors Influencing Nurse Compliance in Implementing Standard Precautions at Hospital X in West Nusa Tengara - Parindra, I Ketut; Menap, Menap; Khalik, Abdul; Sastrawan, Sastrawan; Saimi, Saimi; Sulaiman, Lalu (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to analyze factors influencing nurses' compliance with standard precautions at Hospital X in West Nusa Tenggara, Indonesia. Compliance with these precautions is essential for preventing healthcare-associated infections (HAIs), yet adherence among nurses remains inconsistent. Understanding the determinants of compliance is crucial for improving infection control practices and ensuring patient safety, particularly in resource-limited settings. A quantitative descriptive-analytic design was employed, involving 221 nurses selected through simple random sampling. Data were collected using structured questionnaires and analyzed using Chi-square and logistic regression tests. The findings revealed that 74.7% of nurses demonstrated compliance, 24.4% had moderate compliance, and 0.9% were non-compliant. Several factors significantly influenced compliance, including education level (p = 0.047), knowledge (p = 0.005), infection prevention and control (IPC) training (p = 0.013), management support (p = 0.000), supervision (p = 0.000), and infrastructure availability (p = 0.000). Among these, infrastructure availability emerged as the most dominant factor, with compliance reaching 93.2% in well-equipped environments. The study highlights the importance of structured training programs, strong managerial support, and adequate infrastructure to enhance compliance with standard precautions and reduce HAIs. Strengthening these aspects is particularly crucial in resource-limited healthcare settings. Future research should focus on designing and evaluating intervention strategies to sustain high compliance rates and further mitigate the risks associated with HAIs.